Exploring the Impact of Students’ Listening Needs on the Development of Lecturers’ Pedagogical Competence in Intensive Listening Courses - Hasriani G, Hasriani G; Risan, Rahmad; Muhayyang, Maemuna; Aeni, Nur; Cardoso , Luís (JOLLT Journal of Languages and Language Teaching, 2026)
In the context of English as a Foreign Language (EFL) in higher education, Intensive Listening courses are expected to prepare students for the demands of academic listening yet teaching practices do not always align with students’ actual needs. This study explores the impact of students’ listening needs on the development of lecturers’ pedagogical competencies in Intensive Listening courses. Using a mixed-methods needs analysis design, data were collected from 120 students in three classes through questionnaires, classroom observations, and semi-structured interviews. Questionnaire data were analyzed using descriptive statistics, while observation and interview data were analyzed thematically and combined through triangulation. The research findings indicate that students prioritize academic listening as their primary goal, but still struggle with lexical density, high speech rate, accent variation, and note-taking when dealing with long spoken texts involving multiple speakers. Students also strongly prefer multimodal and scaffolded activities, particularly video-based materials supported by transcripts or subtitles and clear guidance at the pre-listening, during-listening, and post-listening stages. These needs point to specific areas where lecturers’ pedagogical competencies need to be strengthened, including planning and designing academic listening tasks, implementing process-oriented instruction and strategies, and implementing assessments that truly reflect the demands of academic listening. This study proposes the EPMT (ESP-informed, Process-oriented, Metacognitive, and TPACK-supported) model as a practical framework for aligning Intensive Listening pedagogy with students’ needs.